Проблемы и перспективы использования в металлургии углей и продуктов их переработки - Потапов, Б. Б.; Пинчук, В. А. (НТУ "ХПИ", 2006)
The directions of usage of coal in metallurgy are reviewed as primary fuel at recovery of iron-ore raw, at an insufflations of braize in blast furnaces, coal gasification for further usage as fuel and reducing gas. The power and ecological efficiency of a pairs - oxygen gasification low-grade coals with separation of a sol part by the way of melt is justified. Is rotined, that the economic feasibility of implementation of such process can be reached by salvaging a physical heat of products of process, and also manual production of granulouse leach and concentrate of infrequent trace substances.
Keywords: металлургия; промышленность Украины; черная металлургия; уголь; первичное топливо; пылеугольное топливо; газификация угля